Aplicación de un programa de enriquecimiento ambiental y evaluación de la respuesta conductual del Oso Andino (tremarctos ornatus) cautivo en el bioparque Orillas del Zamora. - Rojas Román, Luis David (2019)
In order to evaluate the effect of a program of environmental enrichment on the behavioral response of animals in captivity conditions, in this study we have worked with two adult captive Tremactos ornatus in the "Orillas del Zamora Biopark”, which were evaluated from November 2018 to January 2019, through two monitoring phases, firstly with a preliminary observation and another phase of control and application of a program of environmental enrichment, program was carried out in which some stimuli were applied. In both phases, behavioral variables were evaluated, first based on the presence of visitors in the Biopark and then by assessing the behavior of individuals before and after each environmental enrichment was applied. To evaluate these variables, ethograms were made, which were constructed from the preliminary observation; through these parameters we calculated the frequency of each behavior pattern, for which the two samples were observed through focal sampling, for 60 minutes in the morning (10:30 - 11:30) and in the afternoon (3:00 - 4:00), with a sampling effort of 34 hours, distributed into 6 weeks of observation. Since there was a control phase to compare with, it was found that the male individual decreases the stereotyped behaviors after the application of the stimuli, in the same way the female decreases rest and inactivity behaviors, increasing in both individuals’ activities of interaction with their partner. In general, the stimuli exerted a significant effect on the behavioral response of individuals. Finally, a didactic guide was adapted with the environmental enrichments of greater acceptance by the individuals, with the purpose of assuring the welfare of the animals throughout their captive life. Key words: Andean bear, Ex situ conservation, Ethology, Animal welfare, Stereotypes.